The Effects of Organizational Health on the Knowledge Sharing - Mudhafar Hamad Ali; Ronyaz Hayyas Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The current research aims to demonstrate the role of organizational health in knowledge sharings dimensions. Organizational health is considered an independent variable with its sub-dimensions (leadership of tasks, needs of survival, needs of growth and development), while knowledge sharing is deliberately variable in its sub-dimensions (individual, organizational, technological), where the aim of the research is to achieve the set of goals, most important of which is the reality of the colleges investigated in the use of the variables and the description of the dimensions of organizational health and knowledge sharing, and test correlation relationship and impact between them In order to reach the goal of the research, a hypothesis was designed to search through a set of hypotheses. In order to ascertain the validity of the hypotheses, all of them were subjected to multiple tests. The questionnaire was used as a means of obtaining data. The research was followed by the analytical descriptive method, where the main and sub-variables were described, as well as for the analysis of relations and the effect between the variables. The number of responding individuals reached (247) members of the teaching staff in the research faculties. The hypotheses were tested through the application of statistical methods by the software (SPSS V.25). The research found a number of main conclusions. The results of the correlation analysis revealed a positive and high level of relationship between organizational health and knowledge sharing at the macro and micro levels. In addition, there was a positive and significant effect on the organizational health variable in the knowledge sharing variable, as indicated by the macro and partial analysis indicators. The research proposed a set of proposals, the most important of which is the need to focus the research faculties on the optimal investment of organizational health dimensions, as a guide towards knowledge sharing. The research also proposed developing and developing the organizational innovation capacity continuously by the senior management by encouraging its creative faculty and giving it some privileges and incentives to notice it The fruit of its effort and excellence,